Differences in p53 and Bcl-2 expression in relation to cell proliferation during the development of human embryos. Issue 3 (June 1998) - Lichnovský, V; Kolár, Z; Murray, P; Hlobilková, A; Cernochová, D; Pospísilová, E; Vojtĕsek, B; Nenutil, R
Abstract : AIMS: To study the patterns of p53 and Bcl-2 expression in relation to cell proliferation during human embryogenesis in order to help elucidate their potential roles in the regulation of cell proliferation and apoptosis during morphogenesis. METHODS: Immunohistochemistry for p53, Bcl-2, and proliferating cell nuclear cell antigen (PCNA) proteins was performed, using a variety of monoclonal antibodies, on paraffin was embedded sections of tissues from 68 human embryos and fetuses of between 4 and 30 weeks gestation. RESULTS: Positive relations between sites of proliferative activity (as detected by PCNA expression) and p53 expression were found in the kidney, early developmental stages of intestine and lungs, liver, pancreas, heart, and in embryonic osteoblasts. On the other hand, positive relations between proliferative activity and Bcl-2 expression were found in the gonads, adrenal glands, in the cells of the dental lamina, hair follicles, syncytiotrophoblast, chondrocytes, and more advanced stages of intestinal development. In tissues of the central nervous system, p53 and Bcl-2 were co-expressed at the same sites but there was an inverse relation between p53/Bcl-2 expression and proliferative activity. CONCLUSIONS: These data suggest that p53 and Bcl-2 have tissue specific and stage specific functions during embryogenesis.